2003
DOI: 10.1016/s1525-0016(02)00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Free cationic liposomes inhibit the inflammatory response to cationic lipid–DNA complex injected intravenously and enhance its transfection efficiency

Abstract: In this report, we show that intravenous (i.v.) injection into mice of a complex made of the cationic lipid diC14-amidine and the luciferase reporter plasmid (pCMV-luc) results in efficient gene expression in several organs but elicits an inflammatory response characterized by a release of tumor necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma) into the serum of treated animals. A single preinjection of free diC14-amidine liposomes improves the i.v. transfection efficiency of the diC14-amidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…These results are contrast to the previous reports on decrease in cytokine production and increase in transgene expression by preinjection of free liposomes and coinjection of NF-kB decoy ODNs. [10][11][12] When we preinjected lipopolysaccharide which induces the inflammatory responses into mice, it suppressed transgene expression from the same plasmid DNA as used in this study by ca. 80-fold (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are contrast to the previous reports on decrease in cytokine production and increase in transgene expression by preinjection of free liposomes and coinjection of NF-kB decoy ODNs. [10][11][12] When we preinjected lipopolysaccharide which induces the inflammatory responses into mice, it suppressed transgene expression from the same plasmid DNA as used in this study by ca. 80-fold (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9] To overcome the inflammatory response associated with the cationic lipid-mediated gene transfer, preinjection of free liposomes and coinjection of NFkB decoy oligodeoxyribonucleotides (ODNs) have been attempted. [10][11][12] These treatments decrease cytokine production and increase transgene expression. The inflammatory response elicited by the DNA-cationic lipid complexes is thought to be due to unmethylated CpG sequences, because the unmethylated CpG dinucleotides in ODNs effectively induce cytokine production.…”
mentioning
confidence: 99%
“…Short-chained lipids are more fusogenic than long-chained ones, and liposomes composed of cationic lipids of different acyl chain lengths fuse more easily than those made up of lipids with identical acyl chains [12]. DiC14-amidine, a shortchained cationic lipid, has been reported to posses a high level of transfection activity even in the absence of helper lipids in vitro and in vivo [13,14]. It was also recently successfully used as an immunoadjuvant [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Liu et al [26,27] incorporated non-steroidal anti-inflammatory drugs (dexamethasone and prednisone) and agents that inhibit NF-κ B (capsaicin) and MAPK (PD9805) inflammatory pathways into the lipid bilayer of lipoplex, and showed that the levels of inflammatory cytokines (TNF-α , IL-12 and IFN-γ ) were reduced by 2-to 10-fold. Elouahabi et al [22] showed that a single pre-injection of empty DiC14-amidine liposomes reduced TNF-α production by 2-to 3-fold induced by the subsequent DiC14-amidine/protamine/pDNA complex, which in turn increased the transgene expression by 40-fold. This interesting result, however, was contradictory to their earlier report indicating that the DiC14-amidine liposomes induced significant production of inflammatory cytokines, including TNF-α [14] .…”
Section: Lipoplex Induces Systemic Inflammation Which In Turn Reducementioning
confidence: 99%